2015
DOI: 10.1113/jphysiol.2014.281196
|View full text |Cite
|
Sign up to set email alerts
|

Differential function of Gγ13 in rod bipolar and ON cone bipolar cells

Abstract: Key pointsr The G-protein-mediated metabotropic glutamate receptor 6 (mGluR6) signalling cascade is critical for light responses in all retinal ON bipolar cells. The present study evaluates the role of G-protein subunit Gγ13 in ON bipolar cells by deleting the mouse Gng13 gene.r Gγ13 is a partner of Gβ3 in all types of retinal ON bipolar cells, and contributes to generating the light response.r Gγ13 also contributes to maintenance because, in its absence, the light response decreases with age.r Three independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…; Ramakrishnan et al. ). Although Rampino and Nawy () found that TrpM1‐evoked currents were regulated by the PIP 2 ‐PLC‐PKC signaling pathway, gain control mechanisms by group I mGluRs have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…; Ramakrishnan et al. ). Although Rampino and Nawy () found that TrpM1‐evoked currents were regulated by the PIP 2 ‐PLC‐PKC signaling pathway, gain control mechanisms by group I mGluRs have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that in ON bipolar cells, deleting Gβ3 dramatically reduces Gα o and Gγ13 (Dhingra et al ., ). Surprisingly, deleting Gγ13 greatly reduces Gβ3, but hardly affects the expression of Gα o (Ramakrishnan et al ., ). To test whether these relationships are reciprocal, we tested how the deletion of Gα o1 , the primary splice variant in ON bipolar cells, affects its partners.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, Gγ13 was described as the most prominent isoform present in ON-BCs (Dhingra et al 2008, Huang et al 2003). However, elimination of Gγ13 in mice only partially affected ON-RBC responses with no appreciable effects in ON-CBC (Ramakrishnan et al 2015). Thus, while Gβ3γ13 appears to be the major species involved in mGluR6 signaling in ON-RBCs, other Gβγ dimers might play a role in signaling in both ON-RBCs and to a greater extent in ON-CBCs.…”
Section: Heterotrimeric G Proteins Transfer Light-evoked Signals Frommentioning
confidence: 99%
“…Thus, while Gβ3γ13 appears to be the major species involved in mGluR6 signaling in ON-RBCs, other Gβγ dimers might play a role in signaling in both ON-RBCs and to a greater extent in ON-CBCs. Indeed, several additional proteins have been identified to be enriched in ON-BCs including Gβ4, γ5, γ10, and γ11 (Huang et al 2003, Ramakrishnan et al 2015). It seems possible that this functional heterogeneity of Gβγ combinations may contribute to distinct response properties of ON-BC populations.…”
Section: Heterotrimeric G Proteins Transfer Light-evoked Signals Frommentioning
confidence: 99%